An Investigation Into EFL Learners’ Electronic Feedback Practices During the Coronavirus Pandemic: Support and Challenges - Atef AbuSa’aleek; Eyhab Yaghi (Studies in Self-Access Learning Journal)
Previous research has suggested that e-feedback mechanisms are widely misunderstood, difficult to perform efficiently, and often need to fulfill expectations to affect student performance substantially (Carless & Boud, 2018). To better understand EFL learners’ e-feedback practices, this study aimed to provide a comprehensive picture of EFL learners’ e-feedback practices throughout the pandemic in the general preparatory year college at Majmaah University.